Side-impact collisions of Ar with NO - Heid, C; Walpole, V; Brouard, M; Jambrina, P; Aoiz, F (Springer Nature, 2019)
In the realm of molecular collision dynamics, stereochemistry refers to the dependence of the collision outcome on the mutual orientation of the colliding partners. This may involve directed end-on collisions along a molecular bond axis or encounters in which the partner approaches the bond of an oriented molecule from the side. Using both experiment and theory, we show here that in the simplest case of an inelastic collision between an atom and a nearly homonuclear diatom, in which the two atoms have almost the same mass, the scattering dynamics are very distinct for impacts on either side of the molecule. By recording the direction of the scattered particles after the collision, we demonstrate that the intensity of products scattered in the forward direction, near parallel to the initial motion, can be substantially controlled and even maximized by altering the side-on orientation of the quantum state selected NO molecules that collide with Ar atoms. In addition, our findings provide valuable information about the preferred collision mechanism and reveal interesting quantum interference effects.